Vitruvius Neerlandice. Een nieuwe vertaling van het Romeinse 'handboek bouwkunde' (Bulletin KNOB, 1998)
The significance of Vitruvius's manual for the later periods of art history is unmistakable. The Latin text - often elaborate and quite lapidary in style - poses translation problems for even the most expert classicist or archaeologist. The more welcome is the new, easily readable translation of Ton Peters (l 997), thus opening up Vitruvius' work to the professional, the student or the interested layman.In the accompanying article the person of Vitruvius and his work are clarified on the basis of fragments translated by Peters. The subjects discussed here are the building materials and wall work, Greek and Etruscan temple construction, the basilica of Fano, aspects of the atrium house, wall decoration and some passages from the last two books.